2021
DOI: 10.1371/journal.pcbi.1008617
|View full text |Cite
|
Sign up to set email alerts
|

Aggregative cycles evolve as a solution to conflicts in social investment

Abstract: Multicellular organization is particularly vulnerable to conflicts between different cell types when the body forms from initially isolated cells, as in aggregative multicellular microbes. Like other functions of the multicellular phase, coordinated collective movement can be undermined by conflicts between cells that spend energy in fuelling motion and ‘cheaters’ that get carried along. The evolutionary stability of collective behaviours against such conflicts is typically addressed in populations that underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…The action of selection on properties of isolated cells has been so far largely overlooked when considering the evolution of social traits, with the notable exception of the role of ‘loner’ cells (Dubravcic et al, 2014; Rossine et al, 2020; Miele and De Monte, 2021). Here, we showed that properties of isolated cells can be important not only in fluctuating environments, where different behavioural patterns are effective in hedging cells’ bets in front of unpredictable selective pressures.…”
Section: Discussionmentioning
confidence: 99%
“…The action of selection on properties of isolated cells has been so far largely overlooked when considering the evolution of social traits, with the notable exception of the role of ‘loner’ cells (Dubravcic et al, 2014; Rossine et al, 2020; Miele and De Monte, 2021). Here, we showed that properties of isolated cells can be important not only in fluctuating environments, where different behavioural patterns are effective in hedging cells’ bets in front of unpredictable selective pressures.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, feedbacks between ecology and the resulting evolutionary dynamics essentially influence the fate of cheating (Lion, 2018;Tilman et al, 2020;Weitz et al, 2016). Traits that underpin conflicting strategies within the multicellular phase, but that also affect behaviour of isolated cells -for instance cell motility -have been shown to give rise to eco-evolutionary cycles akin to aggregative multicellular life cycles, where social 'cooperators' and 'cheaters' coexist (Miele and De Monte, 2021). This model predicts that selection for escalating social conflicts drives the emergence of a temporal alternation of solitary living and phases when social conflicts manifest within aggregates.…”
Section: Interplay Of Different Time Scalesmentioning
confidence: 99%
“…Already in 1957 John Tyler Bonner suggested that faster cells would position themselves to the front of the slug, thus becoming stalk with a higher probability (Bonner, 1957). Motility differences have moreover been recently related to the evolutionary emergence of aggregative multicellular life cycles (Miele and De Monte, 2021). However, for heterogeneity in motility at the onset of development to affect cell fate, it is necessary that motility differences are maintained after starvation, something for which there is mixed and indirect evidence.…”
Section: Glucose Concentrationmentioning
confidence: 99%
“…More generally, feedbacks between ecology and the resulting evolutionary dynamics essentially influence the fate of cheating (Lion, 2018;Tilman et al, 2019;Weitz et al, 2016). Traits that underpin conflicting strategies within the multicellular phase, but that also affect behaviour of isolated cells -for instance cell motility -have been shown to give rise to eco-evolutionary cycles akin to aggregative multicellular life cycles, where social 'cooperators' and 'cheaters' coexist (Miele and De Monte, 2021). This model predicts that selection for escalating social conflicts drives the emergence of a temporal alternation of solitary living and phases when social conflicts manifest within aggregates.…”
Section: Interplay Of Different Time Scalesmentioning
confidence: 99%